Combining Teletherapy and On-line Language Exercises in the Treatment of Chronic Aphasia: An Outcome Study - Richard D. Steele; Allison Baird; Denise McCall; Lisa Haynes (International Journal of Telerehabilitation)
We report a 12-week outcome study in which nine persons with long-term chronic aphasia received individual and group speech-language teletherapy services, and also used on-line language exercises to practice from home between therapy sessions.  Participants were assessed at study initiation and completion using the Western Aphasia Battery, a portion of the Communicative Effectiveness Index, ASHA National Outcome Measurement System, and RIC Communication Confidence Rating Scale for Aphasia; additionally participants were polled regarding satisfaction at discharge.  Pre-treatment and post-treatment means were calculated and compared, and matched t-tests were used to determine significance of improvements following treatment, with patterns of independent on-line activity analyzed.  Analysis of scores shows that means improved on most measures following treatment, generally significantly: the WAB AQ improved +3.5 (p = .057); the CETI Overall (of items administered) — +17.8 (p = .01), and CCRSA Overall — + 10.4 (p = .0004).  Independent work increased with time, and user satisfaction following participation was high.